2019
DOI: 10.1142/s1013702519500070
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapist–patient communication in entry-level physiotherapy education: A national survey in Nigeria

Abstract: Background: Clinical communication impacts on physiotherapy treatment outcome and its competence warrants being assessed during training for physiotherapists given the increasing need to improve patient outcomes. Objective: This study aimed to investigate the assessment of clinical communication in entry-level physiotherapy programs in Nigeria. Methods: In a cross-sectional survey, questionnaires were sent by e-mail or hand-delivered to the heads of physiotherapy programs, asking them to consult with faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A reason for this could be having previous knowledge from standard entry-level training that encompasses basic components of psychosocial care and evidence-based practice with an emphasis on communication as described by Abaraogu et al . 53 Other studies show physiotherapists had previous knowledge of the biopsychosocial approach. 54 55 This shows the viability of adopting a stratified care approach and ease of transition among physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reason for this could be having previous knowledge from standard entry-level training that encompasses basic components of psychosocial care and evidence-based practice with an emphasis on communication as described by Abaraogu et al . 53 Other studies show physiotherapists had previous knowledge of the biopsychosocial approach. 54 55 This shows the viability of adopting a stratified care approach and ease of transition among physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous knowledge; Sanders et al reported thoughtful obedience from physiotherapists51 and Odole et al 52 wrote about the willingness of physiotherapists to adopt innovative care methods. A reason for this could be having previous knowledge from standard entry-level training that encompasses basic components of psychosocial care and evidence-based practice with an emphasis on communication as described by Abaraogu et al 53. Other studies show physiotherapists had previous knowledge of the biopsychosocial approach 54 55.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been claimed that 80% of patient complaints are the result of a breakdown in communication [3,7]. Moreover, it is the health care provider's (e.g., physician, athletic trainer, physical therapist), ability to design effective instructions, explanations, bad news messages, reassurance, advice, adherence to therapy regimen, and motivational attempts that are the messages at the core of patient interaction [7][8][9][10][11]. Of these, instructions relative to injury, rehabilitation, and return-to-play and explaining illness appear to be of greatest message importance to physical therapists and athletes [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that this important aspect is often neglected due to time constraints within the curriculum. 8 Hence, the authors felt the need for a comprehensive study of the effects of a structured framework like the SEGUE framework and its efficiency in teaching communication skills to physiotherapy students. 9…”
Section: Introductionmentioning
confidence: 99%